2022
DOI: 10.3390/cimb44020063
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-22-3p and MicroRNA-149-5p Inhibit Human Hepatocellular Carcinoma Cell Growth and Metastasis Properties by Regulating Methylenetetrahydrofolate Reductase

Abstract: microRNAs are small endogenous noncoding RNAs that have emerged as key negative regulators that target gene expression through RISC. Our previous study showed that the methylenetetrahydrofolate reductase gene (MTHFR) plays a key role in one carbon metabolism, which is downregulated by miR-22-3p and miR-149-5p, and that it could exert a potential anti-cancer effect. Whether miR-22-3p/miR-149-5p can regulate MTHFR to exert anti-cancer effects has become the focus of our research. Normal (HL-7702 cells) and cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The potential therapeutic role of miR-22-3p was widely investigated and confirmed in the regulation of angiogenesis by targeting VE-cadherin [ 35 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ].VE-cadherin is a component of adherents of vascular endothelial cells, which controls vascular permeability and inhibits unrestrained vascular growth [ 96 ]. The decreased expression of VE-cadherin is associated with endothelial paracellular permeability, which is observed in CRSwNP [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…The potential therapeutic role of miR-22-3p was widely investigated and confirmed in the regulation of angiogenesis by targeting VE-cadherin [ 35 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ].VE-cadherin is a component of adherents of vascular endothelial cells, which controls vascular permeability and inhibits unrestrained vascular growth [ 96 ]. The decreased expression of VE-cadherin is associated with endothelial paracellular permeability, which is observed in CRSwNP [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in various cancer types, including thyroid cancer, reported that miR-324-5p is generally up-regulated [40]. Several authors investigated the biological role of miR-22-3p, and described it as a tumor suppressor miRNA [41][42][43]. In cervical squamous cell carcinoma, miR-22-3p downregulation has been associated with metastatic tumor progression [44]; the biological functions of miR-22-3p in the context of RAS-mutant thyroid tumors has not been investigated.…”
Section: Discussionmentioning
confidence: 99%